Myxozoans (Cnidaria) do not Retain Key Oxygen-Sensing and Homeostasis Toolkit Genes. (17th January 2023) - Graham, Allie M; Barreto, Felipe S
Abstract: For aerobic organisms, both the hypoxia-inducible factor pathway and the mitochondrial genomes are key players in regulating oxygen homeostasis. Recent work has suggested that these mechanisms are not as highly conserved as previously thought, prompting more surveys across animal taxonomic levels, which would permit testing of hypotheses about the ecological conditions facilitating evolutionary loss of such genes. The Phylum Cnidaria is known to harbor wide variation in mitochondrial chromosome morphology, including an extreme example, in the Myxozoa, of mitochondrial genome loss. Because myxozoans are obligate endoparasites, frequently encountering hypoxic environments, we hypothesize that variation in environmental oxygen availability could be a key determinant in the evolution of metabolic gene networks associated with oxygen-sensing, hypoxia-response, and energy production. Here, we surveyed genomes and transcriptomes across 46 cnidarian species for the presence of HIF pathway members, as well as for an assortment of hypoxia, mitochondrial, and stress–response toolkit genes. We find that presence of the HIF pathway, as well as number of genes associated with mitochondria, hypoxia, and stress response, do not vary in parallel to mitochondrial genome morphology. More interestingly, we uncover evidence that myxozoans have lost the canonical HIF pathway repression machinery, potentially altering HIF pathway functionality to work under the specific conditions of their parasitic lifestyles. In addition, relative to other cnidarians, myxozoans show loss of large proportions of genes associated with the mitochondrion and involved in response to hypoxia and general stress. Our results provide additional evidence that the HIF regulatory machinery is evolutionarily labile and that variations in the canonical system have evolved in many animal groups.